Aristolochiaceae endémicas del Perú - León, Blanca (2006)
The Aristolochiaceae are represented in Peru by 40 species in the genus Aristolochia (Brako & Zarucchi, 1993), all of them vines and lianas. Here we recognize seven endemic species. Most of these endemic taxa are found in the Very Humid Premontane and Humid Lowland Amazonian Forest regions, between 200 and 2000 m elevation, while two species are found in the Dry Forest region. Only one endemic species has been found to date in protected areas.